2015
DOI: 10.1039/c4md00131a
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding cell penetration by stapled peptides

Abstract: A systematic study on cell penetration by stapled peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
301
5
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(334 citation statements)
references
References 41 publications
20
301
5
8
Order By: Relevance
“…Cell penetration is likely to be further enhanced by the overall positive charge carried by SP1, as previous studies have suggested that positive charge is often favorable for uptake of constrained peptides into cells (36). A systematic study of Ͼ200 peptides showed that charges of ϩ1 to ϩ7 are optimal for cellular uptake; as SP1 has a charge of ϩ2, it fits the profile of a peptide that readily enters cells (53). The same study showed that the mechanism of cell uptake of stapled peptides likely involves ATP-dependent endocytosis but is not dependent on caveolin or clathrin.…”
Section: Discussionmentioning
confidence: 87%
“…Cell penetration is likely to be further enhanced by the overall positive charge carried by SP1, as previous studies have suggested that positive charge is often favorable for uptake of constrained peptides into cells (36). A systematic study of Ͼ200 peptides showed that charges of ϩ1 to ϩ7 are optimal for cellular uptake; as SP1 has a charge of ϩ2, it fits the profile of a peptide that readily enters cells (53). The same study showed that the mechanism of cell uptake of stapled peptides likely involves ATP-dependent endocytosis but is not dependent on caveolin or clathrin.…”
Section: Discussionmentioning
confidence: 87%
“…Among the various staple types, the hydrocarbon and triazole staples are among the most stable chemically and the least susceptible to biological degradation. There is ample evidence to suggest that the hydrocarbon and triazole staples enable cell penetration [22,37], which is an important property that allows access to intracellular drug targets. The design principles presented in this review are derived mainly from case studies of these two highly promising classes of stapled peptides, but they can also be applied to the other types of staple.…”
Section: Introductionmentioning
confidence: 99%
“…They include stapled peptides (1,2), cyclic peptides (3-6), or peptide analogs, such as peptoids (7)(8)(9)(10)(11), that can affect intracellular targets by interfering with protein-protein interactions. The prototypical class of CPPs is the arginine-rich peptides, best represented by R9 or HIV TAT CPPs (12).…”
Section: From the Department Of Biochemistry And Biophysics Texas Aandmentioning
confidence: 99%